Development Of Social Studies Learning Media Based On Augmented Reality (AR) As A Historical Literacy Medium - Rizal Akbar Darmawan; Muhamad Parhan (Departement of Mathematics Education, 2023)
This research aims to shape the development of creative teacher skills in combining Augmented Reality (AR) learning media through the Metaverse approach with the Augmented Reality learning method in Social Studies Class VII learning. The development of Augmented Reality AR Media through the Metaverse approach is an innovative learning media device that combines education and technology, so as to create students and teachers who can keep up with technological developments. The Metaverse project has relevance to the changing digital era, this must be optimized so that the presence of the Metaverse can be utilized especially to achieve maximum learning outcomes. IPS subjects at the junior high school level certainly help teachers to explain the material. In social studies subjects there are several combinations of social sciences. This research approach uses a quantitative research approach to quasi-experimental methods. The research location is a junior high school in the city of Bandung with representatives from one school. Namely SMPN 1 Bandung. Of course the results of this study look at how effective augmented reality media is in social studies learning to shape the development of creative skills.